Mode-locked soliton erbium-doped fiber laser using a single-walled carbon nanotubes embedded in polyethylene oxide thin film saturable absorber - Ahmad, F.; Harun, Sulaiman Wadi; Nor, Roslan Md; Zulkepely, N.R.; Muhammad, F.D.; Arof, Hamzah; Ahmad, Harith (Taylor & Francis, 2014)
We demonstrate a simple, compact, and low cost mode-locked erbium-doped fiber laser (EDFL) using a single-walled carbon nanotubes (SWCNTs) embedded in polyethylene oxide (PEO) thin film as a passive saturable absorber (SA). The film with a thickness of 50 μm was fabricated using a prepared homogeneous SWCNT solution with 0.1% loading percentage, which was mixed with a diluted PEO solution and casted onto a glass Petri dish to form a thin film by evaporation technique. The film is sandwiched between two fiber connectors to construct a SA, which is then integrated in an EDFL cavity to generate a self-started stable soliton pulses operating at 1558 nm. The soliton pulse starts to lase at pump power threshold of 17.6 mW with a repetition rate of 50 MHz, pulse width of 0.67 ps, average output power of 0.158 mW, pulse energy of 3.16 pJ, and peak power of 4.43 W.